2022
DOI: 10.3389/fbioe.2022.888177
|View full text |Cite
|
Sign up to set email alerts
|

Nanotechnology Approach for Exploring the Enhanced Bioactivities and Biochemical Characterization of Freshly Prepared Nigella sativa L. Nanosuspensions and Their Phytochemical Profile

Abstract: Nigella sativa is one of the most commonly used medicinal plants as it exhibits several pharmacological activities such as antioxidant, antibacterial, anticancer, antidiabetic, and hemolytic. The purpose of this study was to apply the nanotechnology approach for exploring the enhanced bioactivities of freshly prepared Nigella sativa L. nanosuspensions and the phytochemical profile of N. sativa seed ethanolic extract. In this study, we performed the biochemical characterization of Nigella sativa L. ethanolic ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 55 publications
0
16
0
Order By: Relevance
“…This work demonstrated that the DPPH free radical scavenging activity was greatly enhanced by increasing the quantities of the nanosuspensions and N. sativa extracts. The maximal amount of free radical scavenging activity for nanosuspensions of N. sativa extract was seen at 500 g/mL, according Ali et al [ 74 ]. Thus, the DPPH free radical scavenging activity was dramatically improved by increasing the quantities of the nanofibrous mat.…”
Section: Resultsmentioning
confidence: 99%
“…This work demonstrated that the DPPH free radical scavenging activity was greatly enhanced by increasing the quantities of the nanosuspensions and N. sativa extracts. The maximal amount of free radical scavenging activity for nanosuspensions of N. sativa extract was seen at 500 g/mL, according Ali et al [ 74 ]. Thus, the DPPH free radical scavenging activity was dramatically improved by increasing the quantities of the nanofibrous mat.…”
Section: Resultsmentioning
confidence: 99%
“…Te position of the surface plasmon resonance was checked over three weeks, showing the exact position of suspended AgNPs at the prominent peak at 424.1 nm, as shown in our previous report, confrming the stability of the suspension of AgNPs over the tested period. Qualitative phytochemical analysis of N. sativa seed extract has been widely investigated in many studies by standard protocols and found that it contains carbohydrates, oil contents, diferent types of amino acids and proteins, favonoids, steroids, and alkaloids [66][67][68]. Te Ag ions could be reduced by the action of favonoids, alkaloids, and polyphenols in the N. sativa seed extract [66].…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have reported on the synthesis and formulations of nanosuspensions in many medicinal plants such as Terminalia arjuna [ 9 ], Ginkgo biloba [ 10 ], Mentha arvensis L [ 11 ], Allium cepa [ 12 ], and Nigella sativa L . [ 13 ]. These studies have shown promising results in increasing the bioavailability of natural bioactive compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Such nanosuspension characteristics have greatly increased the bioavailability and effectiveness of hydrophobic medicines [ 17 ]. Nanosuspensions are currently used for revolutionary cancer therapies and nano-drug delivery systems for fighting cancer and inflammatory diseases [ 13 ].…”
Section: Introductionmentioning
confidence: 99%